Pelatihan dan Inovasi Packaging untuk Meningkatkan Daya Saing Kain Tenun Sutera di Desa Walanga, Kecamatan Penrang, Kabupaten Wajo - Rosadi, Sri Hardianti; Nurcaya, Nurcaya; Rijal, Syamsu; Arafah, Muhammad; Ruslang, Ruslang; Winarti, Winarti; Samramadana, Muh Akram; Nurhalisa, Nurhalisa (Universitas Pahlawan Tuanku Tambusai, 2024)
Silk woven fabric is a cultural heritage that has been passed down from generation to generation in Wajo Regency, one of which is in Walanga Village. The increasing demand for silk woven fabric shows that consumers are still interested in it, this also makes it one of the economic drivers in Walanga Village. The increasing demand is not supported by the high bargaining value of silk woven fabric. This is caused by the absence of product packaging. So far, silk woven fabrics have been sold without packaging. Community service activities carried out by partners go through several stages, namely: socialization, training, application of technology, mentoring and evaluation, and monitoring. The objective of this activity is to enhance the market value of silk weaving artisans, thereby contributing to the economic growth of the Walanga Village community. The outcomes of this program indicate improvements in product quality and increased income for the community. Attractive packaging has further boosted the product's market value, positively impacting the community's welfare.